2019
DOI: 10.1021/acsomega.9b00204
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Poly(vinyl alcohol)/Chitosan/Bidens pilosa Composite Electrospun Nanofibers with Enhanced Antibacterial Activities

Abstract: Due to the current challenges faced by the increasing rate of drug-resistant bacteria, attention is gradually shifting from synthetic antimicrobial chemical compounds to natural products that are ecofriendly with a wide spectrum of properties. The aim of this research was to successfully fabricate electrospun nanofibers from poly(vinyl alcohol) (PVA), PVA blended with Bidens pilosa and chitosan composite blends and investigate their potential antibacterial activities against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 19 publications
(50 reference statements)
1
22
0
Order By: Relevance
“…In the case of CS and CS/PVA-PD-FeO NPs (0.01%), treated samples were not observed to have half of the minimum inhibitory concentration (IC 50 ). Several studies reported that chitosan and polyvinyl alcohol showed substantial cell proliferation and a biocompatible nature, which suggests the existence of primary hydroxyl, acetyl, and amine functionalities and its ratio [ 68 , 69 , 70 , 71 , 72 ]. Further, AO/EB fluorescence staining showed a greater number of viable cells in various samples treatment, but in PD-FeO NPs alone, treatment showed fewer apoptotic cells ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of CS and CS/PVA-PD-FeO NPs (0.01%), treated samples were not observed to have half of the minimum inhibitory concentration (IC 50 ). Several studies reported that chitosan and polyvinyl alcohol showed substantial cell proliferation and a biocompatible nature, which suggests the existence of primary hydroxyl, acetyl, and amine functionalities and its ratio [ 68 , 69 , 70 , 71 , 72 ]. Further, AO/EB fluorescence staining showed a greater number of viable cells in various samples treatment, but in PD-FeO NPs alone, treatment showed fewer apoptotic cells ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Electrospinning chitosan with synthetic polymers such as PEO and PVA is the simplest and most effective way to obtain chitosan nanofibers as these polymers can improve the performance of the nanofibers in the process of electrospinning [ 110 , 111 ]. Kegere et al mixed chitosan and Bidens bipinnata extract (EXT) into a PVA solution [ 112 ]. However, during the electrospinning process they found that the nanofibers were broken, beaded, and ribbon-shaped.…”
Section: Antibacterial Materialsmentioning
confidence: 99%
“…The in vitro antimicrobial studies showed pristine chitosan–PVA nanofibers inhibited 75.9 and 86% growth of E. coli and S. aureus , respectively. In contrast, Bidens pilosa -loaded nanofibers inhibited 91% growth of S. aureus , indicating that the presence of Bidens pilosa enhanced the antibacterial effects of the nanofibers [ 86 ]. Levengood et al developed chitosan–PVA nanofibers for skin regeneration application.…”
Section: Fabrication Of Biopolymer-based Hybrid Nanofibersmentioning
confidence: 99%